The influence of celebrity endorser and product quality on brand image with positive word of mouth as an intervening variable - Ivan Afandi; Susi Evanita (Operations Management and Information System Studies, 2023)
The purpose of this study was to analyze the influence of celebrity endorsers and product quality on brand image with positive word of mouth as an intervening variable for users of the online shopping application Shopee in Padang City. The population in this study were all users of the online shopping application Shopee in Padang City. The sampling technique used is non-probability sampling with purposive sampling. The number of samples used is 100 samples. This research was analyzed using Structural Equation Modeling (SEM) with the SmartPLS 3.0 application. The findings of this study are; (1) celebrity endorser has a positive and significant direct effect on brand image, (2) product quality does not have a direct effect on brand image, (3) positive word of mouth has a positive and significant direct effect on brand image, (4) celebrity endorser has a positive and significant direct effect on positive word of mouth, (5) product quality has a negative and significant direct effect on positive word of mouth, (6) celebrity endorser has a positive and significant indirect effect on brand image, (7) product quality has a negative and significant indirect effect on brand image.